2019
DOI: 10.3390/cancers11030324
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Role of the Histone Lysine-Specific Demethylase LSD1 in Cancer

Abstract: Studies of alterations in histone methylation in cancer have led to the identification of histone methyltransferases and demethylases as novel targets for therapy. Lysine-specific demethylase 1 (LSD1, also known as KDM1A), demethylates H3K4me1/2, or H3K9me1/2 in a context-dependent manner. In addition to the well-studied role of LSD1 in the epigenetic regulation of histone methylation changes, LSD1 regulates the methylation dynamic of several non-histone proteins and participates in the assembly of different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 93 publications
3
97
0
Order By: Relevance
“…The Lysine‐Specific histone Demethylases LSD1 and LSD2 are two homologous enzymes that demethylate H3K4me1 and H3K4me2. [ 81 ] LSD1 associates with CoREST or NuRD complex that leads to gene repression, whereas LSD2 in association with the cytokine‐like nuclear factor NPAC is involved in transcriptional elongation. [ 82 ] A linker peptide of NPAC stimulates LSD2 activity.…”
Section: Ptms In Complex With Nucleosomementioning
confidence: 99%
“…The Lysine‐Specific histone Demethylases LSD1 and LSD2 are two homologous enzymes that demethylate H3K4me1 and H3K4me2. [ 81 ] LSD1 associates with CoREST or NuRD complex that leads to gene repression, whereas LSD2 in association with the cytokine‐like nuclear factor NPAC is involved in transcriptional elongation. [ 82 ] A linker peptide of NPAC stimulates LSD2 activity.…”
Section: Ptms In Complex With Nucleosomementioning
confidence: 99%
“…For the 23 patients who acquired 5-FU resistance, 19 cases (82.6%) exhibited strong, 3 cases (13%) moderate, and 1 case (4.4%) weak immunopositivity ( Figure 1E). Conversely, for the 37 exhibited weak or no immunopositivity ( Figure 1E), These results indicated that LSD1 upregulation in CRC tissues is associated with 5-FU resistance in patients. Taken together, our results suggest that LSD1 overexpression is tightly linked to CRC development and 5-FU resistance.…”
Section: Lsd1 Overexpression In Human Crc Tissues Is Correlated With mentioning
confidence: 75%
“…Furthermore, it was also found that LSD1 expression markedly enhanced in GC tissues relative to the normal tissues, and LSD1 knockdown obviously impaired the proliferation and migration of GC cells. LSD1 is a member of the flavin-dependent LSD/KDM1 demethylase protein family, and is reported as a transcription repressor that can demethylate H3K4me1/me2 [29][30][31][32] . To explore the related signals and underlying targets that participate in the regulation of LINC01446-LSD1 axis in GC on an unbiased basis, we conducted high-throughput RNA sequencing following the knockdown of LINC01446 in SGC7901 cells.…”
Section: Discussionmentioning
confidence: 99%